La nueva política evangélica: el movimiento evangélico y el complot católico en La Argentina = The New Evangelical Politics : the Evangelical Movement and the Catholic Plot in Argentina - Marostica, Matt (Ciencias sociales y religión, 2000)
The article examines the use, by Argentine Evangelical leaders, of a theory of Catholic conspiracy against the Evangelical movement. The conspiracy frame carries a powerful cultural resonance in Argentina and, we demonstrate, has served to mobilize pastors and lay members to unanticipated levels of political action. Using data from the Evangelical periodical, El Puente, we see the idea of an anti-Evangelical plot appear in the pages of the periodical in moments of heightened political activity by the movement’s leadership. These data suggest the importance of research regarding the cultural theme of the conspiracy and, also, concerning the framing mechanisms that religious leaders use to mobilize political action from the base.